About One of Burials of Novotitorovka Culture From the Territory of Kuban - Mariya A. Balabanova (Vestnik Volgogradskogo Gosudarstvennogo Universiteta. Seriâ 4. Istoriâ, Regionovedenie, Meždunarodnye Otnošeniâ, 2017)
The article is devoted to the burial complex and the skull of the Novotitorovka culture from burial no. 35 of the Ovalny burial mound, Kalininsky district of the Krasnodar region. The burial itself was non-inventory, but it was synchronous with burial no. 26. Both burials were excavated from the level of the ancient surface and covered by the same barrow.